Interstellar space biology via Project Starlight. (January 2022) - Lantin, Stephen; Mendell, Sophie; Akkad, Ghassan; Cohen, Alexander N.; Apicella, Xander; McCoy, Emma; Beltran-Pardo, Eliana; Waltemathe, Michael; Srinivasan, Prasanna; Joshi, Pradeep M.; Rothman, Joel H.; Lubin, Philip
Abstract: Our ability to explore the cosmos by direct contact has been limited to a small number of lunar and interplanetary missions. However, the NASA Starlight program points a path forward to send small, relativistic spacecraft far outside our solar system via standoff directed-energy propulsion. These miniaturized spacecraft are capable of robotic exploration but can also transport seeds and organisms, marking a profound change in our ability to both characterize and expand the reach of known life. Here we explore the biological and technological challenges of interstellar space biology, focusing on radiation-tolerant microorganisms capable of cryptobiosis. Additionally, we discuss planetary protection concerns and other ethical considerations of sending life to the stars. Highlights: NASA Starlight program details a path to send small relativistic spacecraft to interstellar space. Relativistic spacecraft can transport seeds and live organisms to characterize and expand life. Biological and technological challenges of interstellar space biology are outlined. Guidelines for species selection based on research practicality and survivability are offered. Current planetary protection regulations cannot address ethics of extrasolar biology missions.